Informal networks, informal institutions, and social exclusion in the workplace: insights from subsidiaries of multinational corporations in Korea - Horak, Sven (Journal of business ethics, 2023)
Drawing on interviews with decision makers in multinational corporations (MNCs) in South Korea, we examine the role of informal networks in the social exclusion of women in the workforce. Although legislation in the country is in favor of gender equality, we found that informal barriers in the workplace remain difficult to overcome. Informal networks in Korea, yongo, present an ethical issue in the workplace, as they tend to socially exclude women, limiting possibilities for their participation and career progression. We found that informal networks are pervasive and strong because of the informal institutions in which they are embedded and that there is a complex interplay between informal networks and informal institutions that socially excludes women. Due to difficulties accessing yongo, women appear to build inmaek, a network type that is more open and accessible. We also found that MNCs in Korea can compensate for the lack of local informal networks for their female employees. However, despite providing a more supportive environment for women at work, gender equality policies in MNCs are not yet as effective as they could be due to the dynamics of the workplace and the fact that the policies are not tailored to the local context. We have seen evidence in recent years that MNCs can serve as role models for implementing gender equality policies by creating a more inclusive work environment and demonstrating leadership commitment and support.